113 Incidence of migraine and treatment patterns in UK primary care. Issue 12 (14th November 2019) - Yelland, Eleanor; Ghosh, Rebecca; Murray-Thomas, Tarita; Williams, Alison; Hacking, Victoria
Abstract : Objectives: To estimate the incidence of migraine and describe treatment patterns for an indicative year. Methods: Patients ≥18 years old in the Clinical Practice Research Datalink with an incident diagnosis of migraine between 01/04/2007–31/07/2017. The incidence of migraine was estimated. Treatment groups were categorised as none, acute only, prophylactic only, acute and prophylactic. 12-month treatment patterns amongst patients initiating prophylactic treatment with amitriptyline, propranolol or topiramate were classified as continuous use, augmentation, switching or discontinuation. Treatment adherence was defined as medication possession ratio (MPR); patients were 'adherent' if their MPR was ≥0.80. Results: 89, 442 patients with incident migraine were included. Mean age at diagnosis was 40 years [SD 15]; 76.6% were females. The cumulative incidence of migraine rate was 25.8/10, 000 person-years [95%CI: 25.6–26.0]. 86.7% of patients received prophylactic and/or acute treatment; 37.6% and 20.1% had received ≥2 and ≥3 prophylactic treatments, respectively. 1, 636 patients initiated prophylactic treatment in 2015. Propranolol (47.8%) and amitriptyline (47.4%) were most commonly prescribed. Although 80–85% of patients were adherent while on treatment, only 20–30% continued treatment up to 12 months. Conclusions: Migraine treatment remains a challenge. Most patients receive one or more pharmacotherapies but the majority discontinue prophylactic treatment within 12 months of initiation.